„Ta Ukraina, to ona w wojnie i w wojnie…”. Wyobrażenia o przeszłości w życiu społecznym Zachodniej Ukrainy po 1991 roku - Linkiewicz, Olga (Kultura i Społeczeństwo, 2015)
Research by students of the Institute of Ethnology and Cultural Anthropology of the University of Warsaw, conducted in the years 1992–2010 in various regions of western Ukraine, shows that in rural communities and in areas with low levels of urbanization local ties and knowledge transmitted within the family circle and the neighborhood community play a large role in maintaining identity and a strong group separateness. An important element of local knowledge is imagining about the past. This article describes selected ideas about past and recent history. The author suggests that knowledge about the past is read and interpreted within the framework of a religious worldview, which constitutes the basis of the common cosmology of the communities examined. Hence local narratives about the past have a different nature, and vary both from historiography and from the dominant transmissions in the western Ukrainian national discourse of collective memory. They are actualized in daily life and serve to build adaptive social strategies.